(Re)negotiating refugee protection in Malaysia: implications for future policy in refugee management - Katrina Munir-Asen (Deutsches Institut für Entwicklungspolitik (DIE), 2018)
Malaysia provides an interesting case study of the challenges of refugee integration, and the considerable implications of a country continuing to host refugees outside a refugee law framework and without a consistent refugee policy. The Malaysian government has not signed the 1951 United Nations Convention Relating to the Status of Refugees, nor its 1967 Protocol, and is therefore under no obligation to comply with the substantive provisions of it. It has neither implemented relevant legislation nor consistent policy measures to (a) administer refugee status or (b) adequately meet refugees' protection needs. Consequently, with the tacit agreement of the Malaysian government, the United Nations High Commissioner for Refugees (UNHCR) carries out a significant role in the provision of protection activities in the country – along with civil society groups, non-governmental organisations (NGOs) and community-based organisations (CBOs). This paper examines the policy context for refugees in Malaysia, unpacking (a) key challenges faced by refugees in the country, (b) the lessons that can be learned from current ways of working with refugees in non-camp/urban settings, and (c) how policy measures can be strengthened to most effectively protect refugees in the medium- to long-term and, essentially, to foster integration. The paper first considers the history of refugees in Malaysia, and current drivers of flight, before turning to legislation on, and policy implications for, the protection space. Why Malaysia becomes a destination country at all and the (in)formal structures in place to assist integration are discussed, with specific attention paid to the challenges and opportunities presented in urban environments. The paper concludes by providing key recommendations for development practitioners, researchers and policy-makers in the strengthening of refugee protection in Malaysia.
Keywords: 330; Flucht und Migration